Tool Life of Coated Carbide Cutting Tool when Turning Hardened Stainless Steel under Minimum Quantity Lubricant Using Castor Oil - Elmunafi, M.; Noordin, M.; Kurniawan, Denni (2015)
© 2015 Cutting fluids have been used successfully in machining to extend tool life of the cutting tool, but the issues related to environment, health, and manufacturing cost suggest lessening their use whenever possible. Minimal quantity lubrication (MQL), which sprays small amount of cutting fluid (in the range of approximately 10 – 100 ml/h) to the cutting zone area with the aid of compressed air was an alternative for this. Vegetable oils are considered for use in MQL due to their good lubrication and high-pressure performance. This study evaluates the performance of coated carbide cutting tools in term of tool life under MQL with flow rate of 50 ml/h using castor oil as the cutting fluid. The workpiece is hardened AISI 420 stainless steel (with 47 – 48HRC hardness). The performance evaluation was done under different cutting speeds (of 100, 135 and 170 m/min) and feeds (0.16, 0.2 and 0.24 mm/rev). The cutting tool performs well at all cutting parameters combinations. Empirical models for tool life as a function of cutting speed and feed was developed within the range of cutting parameters evaluated. It was found that tool life is inversely proportional to both cutting speed and feed, with the effect of cutting speed is more significant than feed.